Exploring the Interplay of Self-Regulated Learning, Critical Thinking, and Scientific Communication: Insights from International Biology Learners - Luta Fernandez; Mark Gil Vega; Ema Nur Wahyuningsih (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to investigate the relationship between self-regulated learning (SRL) and students’ critical thinking and scientific communication skills in Biology learning. Specifically, it aims to describe students’ SRL, critical thinking, and communication levels, and analyze how SRL influences both skills in a multicultural bilingual context. Methodology: This study employed an explanatory sequential mixed method. The quantitative phase involved 60 grade XI students at Sekolah Indonesia Davao using total sampling, with data collected through SRL questionnaires, critical thinking tests, and scientific communication rubrics. The qualitative phase involved three students and two teachers via semi-structured interviews. Data were analyzed using descriptive statistics, regression, and Miles–Huberman’s model. Main Findings: The findings showed students’ SRL was moderate to high (M = 3.70), strongest in goal setting and weakest in environmental control. Critical thinking (M = 3.53) and scientific communication (M = 3.51) were moderate, with strengths in problem clarification and claim–evidence–reasoning, respectively. Regression analysis revealed SRL significantly predicted both critical thinking (R² = 0.37) and scientific communication (R² = 0.34). Novelty/Originality of this study: This study offers novel insights by integrating self-regulated learning, critical thinking, and scientific communication within Biology education in an international school context. Unlike previous research limited to two constructs, it empirically shows how SRL simultaneously predicts both skills, thereby advancing understanding of how metacognitive regulation fosters cognitive and communicative competencies in science learning.